The Dispute Settlement Model of Regional Head Election Perspective Theory of Legal System in Indonesia - Dedi Mulyadi; Tanti Kirana Utami (UIN Sunan Gunung Djati Bandung, 2017)
The effectiveness of law enforcement depends on three law aspects; those are the structure of law, the substance of the law, and legal culture. Law structure is about the law enforcers, law substance is about the legislative means, and law culture is about a living law adopted by society. This study defines the background of simultaneous regional head elections in Indonesia, the problems of the simultaneous regional head elections in Indonesia, and the implementation of legal system theory to solve the simultaneous regional head election problems in Indonesia. The research method used is normative juridical with the specification of descriptive analysis research. The result of the research is needed permanent law structures that cover (Election Police, Election Prosecutor, Election lawyer, and Election Jury), the law substance through the issuing of general regulations (lex general) which can integrate the Laws of Legislative, Presidential, and Regional Head Elections (lex specialist) and the legal culture of society as human behavior (including the legal culture of law enforcement officers) on the electoral law and law system that are in force at the moment.